Cannabinoid treatments for anxiety: A systematic review and consideration of the impact of sleep disturbance. (December 2022) - Narayan, Andrea J.; Downey, Luke A.; Manning, Brooke; Hayley, Amie C.
Abstract: Cannabidiol's (CBD) safety profile and broad action has made it a popular treatment option for anxiety and co-occurring sleep disturbance. However, its efficacy in healthy and clinical populations, treatment duration, formulation and doses for optimal therapeutic benefits remains unclear. Selected databases were examined from inception to October 2022. Study selection, data extraction and Cochrane Risk of Bias assessments were conducted according to PRISMA guidelines and registered on the PROSPERO database (CRD42021247476) with 58 full-text studies meeting the eligibility criteria and administered CBD only or with Δ-9-tetrahydrocannabinol (THC) across healthy and clinical populations. In healthy populations and certain non-cannabis using clinical populations, CBD had greater anxiolytic effects without prominent effects on sleep. An inverted U-shaped dose relationship, and CBD ratio to THC in combined treatments likely moderated these effects. Mechanistically, observed CBD effects occurred via primary modulation of the endocannabinoid system and secondary regulation of neuroendocrine function. Additional research is needed to understand CBD mechanisms of action across diverse groups. Highlights: Cannabidiol (CBD) treatments for anxiety and disrupted sleep lack clarity. A systematic review was performed on anxiolytic and sedative effects of CBD. CBD had greater anxiolytic effects in certain populations. Inverted U-shaped dose relationship and CBD:THC ratios moderated effects. More research is necessary to confirm its mechanisms of action.